Lebaran Kranggan: Al-Tārikh al-maḥallī li taqālīd mujtama‘ Buhun fi Jāwah al-Gharbīyah - Dian Yasmina Fajri; Susanto Zuhdi (Studia Islamika, 2022)
Rituals associated with Idul Fitri or Lebaran, as well as pilgrimages to the Buhun community's ancestral tombs, are hidden realities behind the scenes of everyday life. This annual tradition known as Lebaran Kranggan features olot (traditional elders) as the central character in ceremonies at the olot traditional house and pilgrimages to the Buhun community's ancestral graves. Buhun's traditional beliefs include animism with Islam. Together with social and political developments, the Buhun community's traditions and identity are under threat of extinction. Thus yet, no extensive local history research on Lebaran Kranggan has been conducted. In order to preserve the Buhun community's identity, Lebaran Kranggan's role as a vehicle must be clarified. By primarily utilizing oral historical materials and oral traditions, this study integrates a historical viewpoint and local history approaches to provide a fresh perspective on Indonesia's traditional beliefs.